Spreading the gains? Prospects and policies for the development of regional value chains in Southern Africa - Anthony H. Black; Lawrence Edwards; Faizel Ismail; Brian Makundi; Michael L. Morris (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2019)
Regional integration is making steady progress in Africa and a key objective is to improve the prospects for industrialization by expanding the regional market. This paper draws on a combination of trade data analysis and industry case studies to better understand the links and synergies between regional value chains and regional integration. The trade data and case studies of three diverse sectors (apparel, food retailing, and automotive) demonstrate the expansion and diversity of regional trade and regional value chains in Southern Africa. This diverse composition of regional exports is suggestive of an opportunity to further enhance industrial development through intra-regional trade. The long-term sustainability of Southern African regionalism depends on the recognition of the importance of regional industrial policy that takes account of the dynamics driving global and regional value chains and facilitates regional linkages across all these sectors.
Keywords: F15; L62; L66; L67; 330; apparel industry; automotive industry; food retailing; regional integration; Southern African Development Community; value chains